Pengaruh Kualitas Pelayanan Petugas Aviation Security terhadap Kepuasan Penumpang di Bandar Udara Sultan Muhammad Salahuddin Bima - Dafiah; Widagdo, Djoko (Ground Handling Dirgantara, 2025)
This study used a quantitative method with an inferential statistical approach. The instrument used in this study was a questionnaire, which was previously tested for validity through validity and reliability tests. The sample size was determined using the Slovin technique. The number of respondents was set at 100 respondents at Sultan Muhammad Salahuddin Airport, Bima. The analysis used to answer the research questions was simple linear regression analysis with the assistance of SPSS software. The results of this study indicate that aviation security officer service quality (AVSEC) influences passenger satisfaction at Sultan Muhammad Salahuddin Airport, Bima. This is evidenced by the results of the hypothesis test, where the significance value was 0.000 < 0.05 (α), with the calculated T-value > T-table (12.759 > 1.984). Furthermore, the results of this study also indicate that the influence of AVSEC officer service quality contributed 62.4% to passenger satisfaction at Sultan Muhammad Salahuddin Bima Airport. This is indicated by the coefficient of determination (R Square) of 0.624.